How Have Animal Models Increased our Understanding of Human Myopia? - Bullimore, Mark A. (Investigative ophthalmology & visual science, 2025)
The extent to which animal models of refractive development have increased our understanding of human myopia is reviewed. During postnatal development refractive errors converge on emmetropia in young animals but form deprivation disrupts this process. Their eyes compensate for optically imposed myopic or hyperopic defocus and recover from the induced refractive error when form deprivation or optical defocus is removed. All of these features have, to some extent, been observed in young children. The lens paradigm has been further leveraged in animals to investigate the influence of competing optical signals on refractive error. These, in turn, have informed and validated certain myopia control technologies. Short-term choroidal thickening and thinning can be induced by positive and negative lenses, respectively, in both animals and humans, although these changes are much smaller and more variable in the latter. Finally, inconsistencies among animal models, inconsistencies between animal models and human myopia, and knowledge gaps and opportunities are discussed.